Effect of Fly Ash on the Engineering Propertiesof Swelling Soils - Hussein Al-Dahlaki, Mohammed (Journal of Engineering and Sustainable Development, 2007)
This study reports the influence of different percentage additives of fly ash on the swell characteristics and engineering properties of laboratory-prepared heavy clays. For this purpose the effect of 0-25% of fly ash on the swelling properties of expansive soils have been studied on samples with various curing time (0, 10-days and 30-days). Moreover, the effects of such addition on other mechanical properties of expansive soil (such as grain size distribution and consistency limits) are taken into consideration.Fly ash proved its efficiency in improving the swelling characteristics. The results show an increase in swelling reduction with increasing fly ash percent increase and curing time